From eco-anxiety to eco-hope: surviving the climate change threat - Betro’, Sophia (Frontiers in Psychiatry, 2024)
Introduction As the average global temperature increases, the effects of climate change worsen, through effects on worsening extreme events as well as exacerbating political, economic, and social turmoil (wars, conflicts, and migrations). This poses an existential risk to the survival of humans and non-humans. These effects are visible due to the impact on people’s mental health and psychophysical well-being. This article aims to explore the growing phenomenon of psychoterratic syndromes, with focus on the effect of eco-anxiety on mental health. Furthermore, the relationship between eco-anxiety and behavior response (both individual and collective) in the climate crisis era is outlined. Methods A research with interdisciplinary approach was carried out for recent literature and articles relating to psychoterratic syndromes and the effects of climate change on mental health. Results The article explores the effects of climate change on mental health, including various research on the onset of new emotions in response to psychological effects to climate change, called psychoterratic syndromes (such as eco-anxiety, climate anxiety, solastalgia, eco-grief). Among these, eco-anxiety is the most popular term used for describing how people feel about climate change. However, the paradigm that described eco-anxiety only as a pathological emotion needs to be changed. Discussion The article emphasizes the positive effect of eco-emotions and the need to stimulate people to move from a state of anxiety, which could bring apathy and resignation, toward eco-hope. Eco-hope could be an adaptive coping mechanism in people and communities, which is key to preventing, mitigating, and protecting mental and planetary health.